2010
DOI: 10.1007/s10526-010-9307-9
|View full text |Cite
|
Sign up to set email alerts
|

Host size, superparasitism and sex ratio in mass-reared Diachasmimorpha longicaudata, a fruit fly parasitoid

Abstract: We analyzed the relationship among host size, superparasitism and sex-ratio in mass reared Diachasmimorpha longicaudata (Hymenoptera: Braconidae). Individual host pupae of Anastrepha ludens (Diptera: Tephritidae) were measured (length and width), and the number of oviposition scars per pupa was used as a reliable indicator of superparasitism. The probability of an emerging parasitoid being a female was positively associated with the number of oviposition scars on the host cuticle, but not with the host size. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
1
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 37 publications
(42 reference statements)
6
53
1
8
Order By: Relevance
“…Mated females allocate offspring sex according to host size, depositing fertilized eggs on the larger fi fth-instar nymphs and unfertilized eggs on the smaller third-and fourth-instar nymphs; however, after encountering a conspecifi c, females increasingly laid fertilized eggs resulting in both self-and conspecifi c superparasitism (Ito & Yamada, 2016). Montoya et al (2011) and DiazFleischer et al (2015) observed an increasingly femalebiased sex ratio with higher levels of superparasitism in mass-reared Diachasmimorpha longicaudata (Ashmead) (Hymenoptera: Braconidae) attacking fruit fl y larvae, a result confi rmed by fi eld collections of infested mango fruits (Montoya et al, 2013). In contrast, in many gregarious parasitoids, superparasitizing females produce a relatively more male-biased sex ratio as predicted by models of local mate competition (Wylie, 1965;Suzuki & Iwasa, 1980;Suzuki et al, 1984;Godfray, 1994;West, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Mated females allocate offspring sex according to host size, depositing fertilized eggs on the larger fi fth-instar nymphs and unfertilized eggs on the smaller third-and fourth-instar nymphs; however, after encountering a conspecifi c, females increasingly laid fertilized eggs resulting in both self-and conspecifi c superparasitism (Ito & Yamada, 2016). Montoya et al (2011) and DiazFleischer et al (2015) observed an increasingly femalebiased sex ratio with higher levels of superparasitism in mass-reared Diachasmimorpha longicaudata (Ashmead) (Hymenoptera: Braconidae) attacking fruit fl y larvae, a result confi rmed by fi eld collections of infested mango fruits (Montoya et al, 2013). In contrast, in many gregarious parasitoids, superparasitizing females produce a relatively more male-biased sex ratio as predicted by models of local mate competition (Wylie, 1965;Suzuki & Iwasa, 1980;Suzuki et al, 1984;Godfray, 1994;West, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Superparasitism is a specialty of parasitoid females in which an egg is deposited in a host that is already parasitized by another co-specific or by themselves (i.e., self superparasitism) (VAN ALPHEN; VISSER, 1990). Superparasitism might explain the greater emergence of females and the high parasitism rates obtained in ratios of 1:1 (larvae/ females) in the present study, since superparasitism is correlated to the highest ratio of females in the progeny of D. longicaudata (ALVARENGA et al, 2016;GONZÁLEZ et al, 2010;MONTOYA et al, 2011MONTOYA et al, , 2012. In the past, superparasitism was considered to be a female error, attributed to the failure to discriminate an already parasitized host.…”
Section: Resultsmentioning
confidence: 48%
“…Thus, the main objective of the mass production of this parasitoid is higher female production, since the higher the number of females produced, the more efficient and cheap will be their production, and the more accessible will be their use in biological control programs (OLIVEIRA et al, 2014). Thus, knowledge of the factors that maximize female progeny production is essential for the success of the parasitoids rearing aimed at augmentative releases (MONTOYA et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alvarenga et al (2015) (MONTOYA et al,2011(MONTOYA et al, , 2012. No trabalho realizado por Sá (2015) (CAMARGOS, 2010).…”
Section: Fatores Climáticosunclassified